The influence of Magnafloc10 on the acidic, alkaline, and electrodialytic desorption of metals from mine tailings. (15th October 2018) - Pedersen, Kristine B.; Reinardy, Helena C.; Jensen, Pernille E.; Ottosen, Lisbeth M.; Junttila, Juho; Frantzen, Marianne
Abstract: Repparfjorden in northern Norway has been partly designated for submarine mine tailings disposal when the adjacent Cu mine re-opens in 2019. In order to increase sedimentation, the flocculant, Magnafloc10 is planned to be added to the mine tailings prior to discharge into the fjord. This study investigated the feasibility of reducing the Cu concentrations (375 mg/kg) in the mine tailings by applying electrodialytic extraction, including potential optimisation by adding Magnafloc10. In the acidic electrodialytic treatment (pH < 2), Magnafloc10 increased the extraction of Cu from the mine tailings particles from 76 to 86%, and the flocs with adsorbed metals were separated from the tailings solids by the electric field (1 mA/cm 2 ). The electric energy consumption increased with the use of Magnafloc10 (from 17 to 30 kWh/g Cu extracted), due to lower conductivity in the liquid phase and clogging of the membrane by the flocs. In the alkaline electrodialytic treatment (pH > 12), Magnafloc10 reduced the extraction of Cu from 17% to 0.7%, due to the flocs remaining in the tailing slurries. The electric energy consumption per extracted Cu was similar in the acidic and alkaline electrodialytic treatments without the addition of Magnafloc10. In the alkaline electrodialytic treatment, the extraction of other metals was low (<2%), however longer treatment time is necessary to achieve similar Cu extraction as in the acidic electrodialysis. Depending on the target and timescale for treatment, acidic and alkaline electrodialysis can be employed to reduce the Cu concentration in the mine tailings thereby reducing the metal toxicity potential. Highlights: The anionic flocculant Magnafloc10 increased desorption of metals from mine tailings. Magnafloc10 increased the acidic electrodialytic extraction of Cu from 76 to 86%. Magnafloc10 increased the electrodialytic energy consumption to remove Cu by 76%. Extraction of 18% Cu and <2% of other metals was observed in alkaline electrodialysis.